The ambiguous relation between verbal irony understanding and need for cognitive closure: Reports from two studies - Branowska Katarzyna; Koziński Konrad (Psychology of Language and Communication)
Research on individual differences in irony understanding is not sparse, however the need for cognitive closure (NFC) has not been taken into consideration yet. This article presents the results of two studies on the relation between irony understanding and NFC. The Need for Cognitive Closure Scale in a Polish adaptation and a set of short vignettes with ironic statements were used in both studies. Two hundred and fifty-two (Study 1) and 137 (Study 2) participants completed the study. Results of Study 1 showed no statistically significant relation between irony understanding and NFC, while Study 2 showed a statistically significant, negative correlation between the closed-mindedness subscale of NFC and understanding of praise-by-blame irony. Moreover, in both studies, the ratings of playfulness, criticism, and flattery of ironic statements were analyzed.